Bone-kidney axis: A potential therapeutic target for diabetic nephropathy - Yang, Ming; Luo, Shilu; Yang, Jinfei; Chen, Wei; He, Liyu; Liu, Di; Zhao, Li; Wang, Xi (Frontiers in Endocrinology, 2022)
As the main cause of end-stage renal disease (ESRD), diabetic nephropathy (DN) is still lack of effective prevention and treatment. Recently, organ-to-organ communication has become a new focus in the study of disease pathogenesis. Bone, as an important part of the body, can also secrete bone-derived proteins or peptides that act on distal organs in the form of endocrine. As an organ with high metabolism, the kidney carries on signal and material exchange with other organs at any time through circulation. In this review, we briefly introduce bone composition, summarize current status of bone-derived proteins, and discuss their role in the progression of DN. Finally, the "bone-renal axis" as a potential target for early diagnosis and treatment of DN was proposed.